Charge density functional plus U calculation of lacunar spinel GaM4Se8(M = Nb, Mo, Ta, and W). (25th March 2019) - Lee, Hyunggeun; Jeong, Min Yong; Sim, Jae-Hoon; Yoon, Hongkee; Ryee, Siheon; Han, Myung Joon
Abstract: Charge density functional plus U calculations are carried out to examine the validity of molecular J eff  = 1/2 and 3/2 states in lacunar spinel GaM4 Se8 (M = Nb, Mo, Ta, and W). With LDA (spin-unpolarized local density approximation)+ U, which has recently been suggested as a more desirable choice than LSDA (local spin density approximation)+ U, we examine the band structure in comparison with the previous prediction based on the spin-polarized version of functional and with the prototypical J eff  = 1/2 material Sr2 IrO4 . It is found that the previously suggested J eff  = 1/2 and 3/2 band characters remain valid still in LDA+ U calculations while the use of charge-only density causes some minor differences. Our result provides further support for the novel molecular J eff state in this series of materials, which can hopefully motivate the future exploration toward its verification and the further search for new functionalities.